Financial Inclusion as a Tool for Economic Empowerment of Rural Communities - Pemy Chiristiaan; Lucas Wong (Yayasan Adra Karima Hubbi, 2025)
Background. Financial inclusion is one of the main strategies in improving the economic welfare of rural communities. Access to formal financial services can help increase the economic capacity of individuals and communities, but there are still obstacles to their adoption and utilization. Financial literacy factors, infrastructure limitations, and socio-cultural aspects are challenges that affect the effectiveness of financial inclusion in supporting community economic empowerment. Purpose. This study aims to analyze the role of financial inclusion in the economic empowerment of rural communities and identify factors that affect the level of utilization. The main focus of the research is to examine the relationship between access to financial services and increasing people's economic capacity, especially through a financial literacy approach. Method. The research method used is a quantitative approach with a survey technique on 70 respondents who are small business actors in rural areas. Data were collected through questionnaires and interviews, then analyzed using descriptive statistical and regression methods to measure the impact of financial inclusion on community economic empowerment. Results. The results of the study show that access to formal financial services has a positive impact on increasing business and income of rural communities. Financial literacy is an important factor that determines the effectiveness of the use of these services, where individuals who have a better understanding tend to be more productive in managing finances. Financial education and infrastructure support have proven to contribute significantly to accelerating the adoption of formal financial services. Conclusion. Inclusion not only requires access to financial services but also the right educational strategies so that it can be used optimally. The implications of this study show the need for a community-based approach and more adaptive policies to ensure the success of financial inclusion in encouraging the economic empowerment of rural communities.